Projection of Sectoral Value-added: Comparative Analysis of Alternative Methods - Abdul Rashid, Zakariah; Ahmah Khair, Sabaruddin (Universiti Putra Malaysia Press, 1994)
The paper discusses validation of methods used in projecting Malaysian value-added. Three methods of projection, the CDP blow-Up, the final demand blow-Up and the input-Output methods are compared in terms of their accuracy and relative efficiency. The discussion focuses on three aspects. The first aspect deals with the methodological issues, while the second and third aspects, respectively, determine the accuracy by testing their mean errors and efficiency by comparing their variances. The results show that the input-Output method is superior to the other two methods in terms of accuracy (lowest mean error) and efficiency (lowest variance).